Antibacterial and antioxidant activities of methanolic leaf extracts of some Annonaceous plants found in Nakhon Si Thammarat, Thailand - Boonsong Wungsintaweekul (Journal of Applied Pharmaceutical Science, 2023)
The leaves of 20 species belonging to the Annonaceae family were collected and extracted using methanol to obtain scientific data to evaluate their potential use as new sources of medicinal agents. Methanolic leaf extracts 1–20 were subjected to phytochemical screening and a biological activity assay. The multipharmacophore of the natural products with the synergistic action was remarked as the target. The antimicrobial activity assay was done in parallel with the antioxidant activity test. Among these 20 extracts, extracts 1 and 4 exhibited the inhibition of the growth of all the test microbes. Flavonoids and tannins seem to be the main components of this action. Dramatic results indicate that extract 1 was the most active as an antioxidant. This research was the first report on the biological activities of extract 20. Extract 20 exhibited bactericidal activity against Enterococcus faecalis at 1,000 μg/ml. Terpenes might be the main component of this action. This result was related to the antimicrobial activity of extract 2 which contains terpenes and exhibited high antimicrobial activities against Staphylococcus aureus and E. faecalis (minimum inhibition concentration, MIC = 250 μg/ml). These data indicated a promising potential for Annonaceous plants to be used as sources of naturally occurring medicinal agents.
Keywords: Annonaceae, antioxidative activity, antimicrobial activity